Repetitive T1 Imaging Influences Gray Matter Volume Estimations in Structural Brain Imaging - Broessner, Gregor; Ellerbrock, Isabel; Menz, Mareike M.; Frank, Florian; Verius, Michael; Gaser, Christian; May, Arne (Frontiers in Neurology, 2021)
Voxel-based morphometry (VBM) is a widely used tool for studying structural patterns of brain plasticity, brain development and disease. The source of the T1-signal changes is not understood. Most of these changes are discussed to represent loss or possibly gain of brain gray matter and recent publications speculate also about non-structural changes affecting T1-signal. We investigated the potential of pain stimulation to ultra-short-term alter gray matter signal changes in pain relevant brain regions in healthy volunteers using a longitudinal design. Immediately following regional nociceptive input, we detected significant gray matter volume (GMV) changes in central pain processing areas, i.e. anterior cingulate and insula cortex. However, similar results were observed in a control group using the identical time intervals but without nociceptive painful input. These GMV changes could be reproduced in almost 100 scanning sessions enrolling 72 healthy individuals comprising repetitive magnetization-prepared rapid gradient-echo (MPRAGE) sequences. These data suggest that short-term longitudinal repetitive MPRAGE may produce significant GMV changes without any intervention. Future studies investigating brain plasticity should focus and specifically report a consistent timing at which time-point during the experiment the T1-weighted scan is conducted. There is a necessity of a control group for longitudinal imaging studies.